Contribution of Freshwater Aquaculture for Nitrogen and Phosphorus Production in the Changjiang River and Its Impact on Estuarine Environment - Cece SUN; Wentao WU; Jun LIU; Jiaye ZANG (Progress in Fishery Sciences, 2023)
Background and aims Nitrogen (N) and phosphorus (P) are the key factors controlling eutrophication, playing an important role in aquatic ecosystems. Currently, eutrophication is severe in almost all major river basins in China, negatively impacting the structure and function of riverine ecosystems. The Changjiang River is one of the most valuable rivers in China. However, enhanced economic development in the Changjiang River basin has caused many adverse environmental problems. To restore the ecological environment of the Changjiang River, a series of decrees and laws were implemented, such as the "10-year fishing moratorium along the Changjiang River." This lengthy fishing moratorium will almost certainly promote aquaculture in this river basin, likely increasing N and P loadings in the river system and further adversely affecting the watershed-estuarine environment. Owing to the limitations of observations, methodologies, and data, N and P emissions from freshwater aquaculture and their ecological effects are still ambiguous. For this purpose, the total nitrogen (TN) and total phosphorus (TP) emissions caused by freshwater aquaculture in the major provinces along the Changjiang River were estimated using a nutrient transport flux model from 2003 to 2018. The temporal and spatial variations of TN and TP discharges were calculated to determine the potential ecological effects of freshwater aquaculture on riverine material transport and estuarine environments. This work provides a basis for scientific aquaculture planning and environmental management in the Changjiang River basin.This study employs an integrated model to assess the global environment-global nutrient model (IMAGE-GNM), coupling models with hydrology and nutrient delivery, biogeochemistry, and retention. The model describes N and P in feed inputs, fish production, nutrient conversion, and nutrient output. The IMAGE-GNM has already been well applied in the study of N and P sources, retention, and transport in the Changjiang River, demonstrating the model's credibility in estimating the N and P loads of aquaculture. We evaluated the contributions of N and P and their export to the Changjiang River from 2003 to 2018.(a) Annual emissions of TN and TP caused by freshwater aquaculture in the major provinces along the Changjiang River from 2003 to 2018 were (468.41±179.22) Gg/yr (1 G =109) and (52.02±24.08) Gg/yr, respectively. The emissions of TN in the upper, middle, and lower reaches accounted for 10.44%, 66.38%, and 23.18% of the annual TN emissions, respectively; TP in the upper, middle, and lower reaches accounted for 8.60%, 88.45%, and 24.80%, respectively. The area with the most significant TN and TP emissions caused by freshwater aquaculture was Hubei Province, accounting for (29.96±1.71)% and (31.27±4.11)%, respectively. More than 95% of N and P emissions from freshwater aquaculture were generated by provinces around the main stem of the Changjiang River, especially in the Hubei, Hunan, and Jiangxi Province. (b) The TN emissions from freshwater aquaculture along the Changjiang River increased by 213.96%, from 289.19 Gg/yr in 2003 to 618.76 Gg/yr in 2018. The most significant growth in N emissions was observed in the midstream of the Changjiang River basin from 185.38 Gg/yr to 418.70 Gg/yr. The TP emissions increased from 27.94 Gg/yr in 2003 to 73.55 Gg/yr in 2018. The most significant growth in P emissions was also seen in the midstream from 17.57 Gg/yr to 65.94 Gg/yr. In addition, the growth rates of TN and TP emissions decreased after 2016. The N/P ratio (mass ratio) of freshwater aquaculture discharge in the basin ranged from 6.35 to 12.53 and showed a slowly decreasing trend from 2003 to 2018. (c) According to the model, about 60.52% of the N input through freshwater aquaculture was released in its dissolved form, 20.91% remained in particulate form, and 18.57% was completely converted to biomass and organisms. Approximately 20.93% of the P input through feed was released in the dissolved form, 46.67% remained in the particulate form, and 32.40% was completely converted to biomass.The annual TN and TP emissions of freshwater aquaculture from 2003 to 2018 accounted for an increase of 7.93% and 13.65%, respectively, of the TN and TP emissions in 2010 in the Changjiang River basin. Their increasing trend cannot be underestimated, because the higher biological activity and turnover rates of aquaculture may enhance ecological risks such as eutrophication. Thus, more attention should be paid to the impact of aquaculture activities on the water environment in large river basins. Again, the lower N/P ratio may have a mitigating effect on the imbalance in nutrient stoichiometry in the Changjiang River and its estuary. The change in nutrient origin and delivery would cause a disproportionate increase in non-diatom biomass, potentially breaking the offshore ecosystem stability. Therefore, more attention should be paid to freshwater aquaculture and its environmental effects, and relevant laws and regulations should also be implemented to optimize freshwater aquaculture.